Therapeutic Communication With Patients In The Emergency Room Hospital - Mawaddah, Nurul; Handrianto, Wahyu (Al-Hijrah Indonesia, 2023)
Emergency care causes patients fear and anxiety in the face of treatment, so it requires the nurse's therapeutic communication to manage anxiety. This study aims to determine the effectiveness of therapeutic communication in emergency patients who experience anxiety. The research design uses a pre-experimental research design with a one-group pre-test post-test design approach, and a total of 32 respondents with a simple random sampling technique. The results showed that all respondents experienced a decrease in anxiety after therapeutic communication. Therapeutic communication techniques often used are listening, giving open-ended questions, repeating, indicating acceptance, and providing information. Therapeutic communication with patients experiencing emergency conditions is necessary to provide the support patients need. Nurses' understanding of therapeutic communication techniques according to the patient's condition can improve the achievement of nursing care goals and increase the satisfaction of professional nursing services.